Integrating QTL mapping and GWAS to decipher the genetic mechanisms behind the calcium contents of Brassica napus shoots - Xiang, Yanan; Chen, Feng; Shi, Rui; Yang, Tinghai; Zhang, Wei; Zhou, Xiaoying; Wang, Chunyun; Sun, Chengming; Fu, Sanxiong; Wang, Xiaodong; Zhang, Jiefu; Shen, Yue (Frontiers in Plant Science, 2025)
Brassica napus is an important oil crop worldwide, and its shoots are rich in vitamin C, calcium, and selenium. Functional oilseed-vegetable-dual-purpose varieties can increase the subsidiary value of B. napus. Consumption of high-calcium B. napus shoots can effectively help provide essential elements to the human body. To investigate the genetic mechanisms underlying the calcium concentrations of B. napus shoots, quantitative trait loci (QTL) mapping, using a population of 189 recombinant inbred lines, and a genome-wide association study, using an association panel of 202 diverse accessions, were performed. A total of 12 QTLs controlling calcium content were identified using the recombinant inbred line population in five environments. Among them, qCaC.22GY-A05-1 was considered the major QTL, with a phenotypic variation of 10.10%. In addition, 228 single nucleotide polymorphisms significantly related to calcium content were identified using the genome-wide association study in six environments, and they were distributed on all of the chromosomes, except A10. Finally, 10 candidate genes involved in regulating calcium absorption and transport in B. napus shoots were identified. However, no overlapping intervals were found through a comprehensive analysis of the two datasets. These results provide valuable information for understanding the genetic control of calcium concentration in B. napus shoots.